Rapid printing of nanoporous 3D structures by overcoming the proximity effects in projection two-photon lithography - Harnjoo Kim; Rushil Pingali; Sourabh K. Saha (Virtual and Physical Prototyping, 2023)
Large and deterministic 3D structures with nanoscale features and porosities are valuable for various applications but are challenging to print due to the proximity effects that lead to the merging of adjacently printed features. Here, this challenge has been overcome by minimising the proximity effects in projection two-photon lithography (P-TPL), which is a high-throughput photopolymerization-based 3D printing technique. Through empirical studies and physics-based computational models, it is demonstrated that the proximity effects arise from distinct optical and chemical sources. Processing conditions that individually minimise these sources have been identified. These insights have been leveraged to generate an interspersing P-TPL technique capable of rapidly printing 3D structures with features smaller than 300 nm, pores finer than 700 nm, and at rates greater than 0.5 mm2/s per layer. As interspersing P-TPL is up to 50 times faster than conventional point-scanning TPL, it can enable the scalable printing of nanoporous 3D structures.